Accumulator Charging Control with Piezoelectric Based on Fuzzy Algorithm Scheduling - Iswanto Iswanto; Wahyu Sari Agustiningsih; Faaris Mujaahid; Rohmansyah Rohmansyah; Aris Budiman (Universitas Ahmad Dahlan, 2018)
Battery accumulator charging with pizoelectric takes considerable long time so that an energy harvester is needed by using in this study LTC 3588 circuit. However, by using the energy harvester, the pizoelectric cannot be used to charge 12 volt battery, thus a boost converter is needed. The output voltage is too small to increase by using the boost converter so that the output from the energy converter is used to charge four AA batteries. After the voltage of the four AA batteries as much as 4.7 volt is increased by using the boost converter, the batteries can be used to charge accumulator battery 12 volt. To charge the battery to accumulator, scheduling algorithm planted in microcontroller arduino is needed. By using the scheduling algorithm with fuzzy logic in the arduino microcontroller, the microcontroller is able to control schedule of accumulatro battery charging.